Consumer confidence, durable goods purchase and unemployment forecast - Białowolski, Piotr (Wskaźnik ufności konsumenckiej, popyt na dobra trwałe i prognozy bezrobocia, 2014)
Multi-Group Confirmatory Factor Analysis (MGCFA) demonstrated the deficiency of the four original European Commission (EC) items for consumer confidence. Fit of the MGCFA model was unacceptable and without scalar invariance, index comparison between study periods was not permissible. This provided clear motivation for a plausible alternative index specification to comply with requirements for single-dimensionality and meaning invariance throughout the study period. The MGCFA model using a new set of items demonstrated partial metric and partial scalar invariance. Using the structural equation framework, consumer confidence was revealed as strongly interrelated with unemployment forecast and durable goods purchase.
Ekonometria = Econometrics, 2014, Nr 3 (45), s. 42-55
Keywords: consumer confidence; confirmatory factor analysis; durable goods purchase; measurement invariance; unemployment expectations; wskaźnik zaufania; konfirmacyjna analiza czynnikowa; popyt na dobra trwałe; niezmienność pomiaru; prognozy bezrobocia